Illocutionary Act Analysis Of English Tourism Advertisements In Indonesia - Amalia Zahara Widiastuti; Dodi Oktariza; Asridayani Asridayani (Krinok:Jurnal Linguistik Budaya, 2020)
The writer analysis about meanings and illocutionary function as found in Indonesia tourism advertisements. The purpose of this research is to explain meanings and illocutionary function in Indonesia tourism advertisement based on Dell Hymes’s theory (1974) and Searle’s theory (1969).  The method used in this research is descriptive-qualitative method. Technique used in collecting the data is non-observational technique in which the writer only acts as observer and proceed the research by downloading several advertisement about Indonesia tourism and classify words or phrases containing illocutionary function and meanings. On the other hand, method used to analyze the data is referential method. And other that, the data is concluded and displayed by using formal and informal method, where the result of analysis is explained in written form along with the pictures of the tourism advertisements.The results of the analysis are 11 data that have been found, the data are described based on the context of S-P-E-A-K-I-N-G Hymes (1974). Therefore, the 11 data contain an illocutionary function in each of the data, among them are 4 data having directive function, 4 data commissives function, 2 assertive function and 1 expressive function. Out of 11 data found, there are two function illocutionary functions that appeared, which are directive and commissives functions.Keywords: Pragmatics, Illocutionary Act, Context, Advertisements.